Aquatic macroinvertebrates and water quality in the Ventanilla Wetlands Regional Conservation Area, Callao - Canales Cuadros, Harry (2022)
Ten bodies of water were evaluated in the Ventanilla Wetlands located in the Callao region, in Peru, in the months of March and August 2018. The objective was to study the community of aquatic macroinvertebrates and their application to determine the quality of Water. For this, physicochemical parameters were recorded in situ and a 500 µm D-net was used for the biological collection. The values of the physicochemical parameters were in accordance with what is recommended in the national regulations, except for electrical conductivity, which exceeded the limit in water bodies near the sea. The aquatic macroinvertebrates were represented by 17 taxa, including gastropods and arthropods, of which the former were the most abundant (85.5% in March with 2555 organisms/m2 and 74.2% in August with 4422 organisms/m2), and the latter, the most diverse. The Wisconsin Wetland Macroinvertebrate Biotic Index (WWMBI) categorized water bodies as “very poor” and “poor” quality, probably due to the presence of organic matter, gastropod dominance, or heavy metal contamination. Finally, it was reported that electrical conductivity influenced the distribution of aquatic macroinvertebrates. Likewise, it is suggested to develop biotic indices for coastal wetlands in our country.